Impulsive behaviour in interpersonal encounters: Associations with quarrelsomeness and agreeableness. (7th March 2014) - aan het Rot, Marije; Moskowitz, D.S.; Young, Simon N.
<x xml:space="preserve">Abstract</x> Associations between impulsivity and interpersonal behaviours have rarely been examined, even though impulsivity may disrupt the flow of social interactions. For example, it is unknown to what extent the commonly used Barratt Impulsiveness Scale (BIS‐11) predicts impulsive behaviour in social situations, and how behaving impulsively during interpersonal encounters might influence levels of quarrelsomeness and agreeableness. In this study, 48 healthy working individuals completed the BIS‐11 and recorded their behaviour in social situations using event‐contingent recording. Record forms included items representing quarrelsome, agreeable, and impulsive behaviours. BIS‐11 motor impulsiveness scores predicted impulsive behaviour in social situations. Impulsive behaviour was associated, in different interactions, with both agreeableness and quarrelsomeness. Behaving impulsively in specific interactions was negatively associated with agreeableness in participants with higher BIS‐11 motor impulsiveness and positively associated with agreeableness in participants with lower BIS‐11 motor impulsiveness. Impulsive quarrelsome behaviour may cause interpersonal problems. Impulsive agreeable behaviour may have positive effects in individuals with low trait impulsivity. The idea that there are between‐person differences in the effects of state impulsivity on the flow of social interaction deserves further study.